THE EFFECT OF SAVINGS GROWTH, DEPOSIT GROWTH AND CREDIT GROWTH ON PROFITABILITY - Tahu, Gregorius Paulus (Jurnal MBE Manajemen Bisnis, Equilibrium, 2025)
Village Credit Institution (LPD) is a business entity that collects funds from villagers in the form of savings and deposits and then redistributes the funds in the form of credit, where basically LPD itself has the aim of gaining profit. The purpose of this study is to determine the effect of savings growth, deposit growth and credit growth on LPD profitability in Tabanan District. The types of data sources used in this study are qualitative and quantitative data types and use secondary data sources. The population in this study is LPD in Tabanan District which has 12 LPD units. The sampling method in this study is using a saturated sampling technique, where a sample of 12 LPDs was taken as samples with five years of observation so that the number of observations was 60. This study uses a data collection method in the form of a non-participant observation method. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis that has been carried out, it is obtained that savings growth has a positive effect on profitability. While the growth of deposits and credit does not have a significant effect on the profitability of LPD Tabanan District. The limitation of this study is that it only examines Regional Credit Institutions (LPD) in Tabanan sub-district, so the results of this study cannot necessarily be generalized to LPDs in other areas. This study contributes in providing ideas and input on financial management and improving operational systems in managing financial institutions. This study contributes by exploring the influence of savings, deposits and credit growth on profitability in LPDs in Tabanan sub-district, which has not been widely studied in previous studies.